The human path of organizational change - Tarazona Infante, Tulia Silvia (2015)
Organizational change management is presented as a challenge for organizations which mainly focus on administrative tools ignoring the human side of change, which is the main source of difficulties in its implementation. The human path of organizational change is explained through three psychological functioning levels, which channel information through change processing stages. Management indicators for each stage are provided and actions to assure transition through each one are suggested.